Interlude. "But are as the angels which are in heaven" (Mark 12:25). Reimagining a Gender-Ambiguous Heaven in Dorian Electra's ADAM & STEVE Interlude. - Yannick Schlote (Journal for Religion, Film and Media, 2020)
The American singer and songwriter Dorian Electra is a queer phenomenon. Their dandy appearance - the latest album is called Flamboyant (2017) - goes hand in hand with the criticism of toxic masculinity and gender binarism. One of their latest tracks, called "Adam and Steve", is a gay retelling of the Genesis story. It turns on the derogative phrase: It's Adam and Eve, not Adam and Steve that is used to imply an irreconcilable disparity between Christianity and gay love, i.e. queerness in general ...